Static Culture of Scenedesmus dimorphus In Modified Sago Effluents (MSE) - Mohd Izwan Zulaini, Abdul Gani (Universiti Malaysia Sarawak, UNIMAS, 2010)
This study focuses on using sago effluent as the growth medium which will medium minimize the effects of environmental pollution from the sago factories by culturing algae such as Scenedesmus dimorphus for biodiesel production. In this study, sago effluent was treated with a commercial microbial amendment (BakWira MP300) to produce Modified sago effluent (MSE). Then, the algae Scenedesmus dimorphus was grow in MSE amended with different NaHCO3 concentrations (0g/L, 4g/L and 8g/L) as a static culture. The growth of the algae in MSE was compared to Chu Medium. All cultures were left under sunlight for 20 days. To maximise the distribution of nutrient in the medium, an aeration pump was used. In this study the highest biomass was in MSE with 8g/L NaHCO3 concentration with increasing biomass from 55 mg/L on day 0 to 490 mg/L on day 20. The lowest is in MSE with without NaHCO3 concentration which the increasing of biomass from 40 mg/L on day 0 to 300 mg/L on day 20. For lipid extraction in MSE with 8g/L NaHCO3, percentage of lipid produce by Scenedesmus dimorphus was 7.49% w/w. The biomass gained during cultivation of Scenedesmus dimorphus proved that additions of bicarbonate salts (NaHCO3) can increased the growth of Scenedesmus dimorphus.